(Meta)analysis of Policies Addressed to Women during the COVID-19 Pandemic - Kijewska, Barbara; Mrozowska, Sylwia; Mańkowski, Dobrosław (Studia Polityczne, 2024)
During the COVID-19 pandemic, governments took various anti-crisis measures globally to mitigate its social and economic onsequences. Studies on the effects of the pandemic confirm the hypothesis that the costs of such crises are borne to a greater extent by women due to their worse socio-economic position. The subject of the study is state policies addressed to women. The analysis was carried out based on the Global Gender Response Tracker database (United Nations, 2021), which monitors actions addressed to women taken by overnments around the world to combat the pandemic, and covered the relationship between the values of indicators of social, economic and political development of countries and the implementation of government policies addressed to women (gender policies) during the COVID-19 pandemic. The research confirmed that high indicators of socio-economic and political development of countries are strongly correlated with the presence of government policies addressed to women. Regardless of the level of development of the country, the most frequently implemented policy was the one counteracting violence. On the other hand, policies in the field of social protection, the labour market and economic and tax measures were more often pursued in countries with high development indicators.